THE ROLE AND EFFECTIVENESS OF DIGITAL TECHNOLOGIES IN INCLUSIVE EDUCATION - Umedova Musharraf Erkin qizi (The Conference Hub, 2025)
The requirement for an inclusive system in education continues to grow steadily in current times. An environment dedicated to quality learning that also provides equity needs to adapt to different student needs for children with disabilities needs to be created. Traditional teaching methods do not satisfy fully the educational requirements of these students. Contemporary digital technology approaches serve as fundamental tools for building inclusive learning systems. The development of learning trajectories with adapted content and interactive tools becomes possible through digital technologies for students who are hearing or vision impaired. The initiative promotes equality by bringing inclusivity together with high educational standards.